2018
DOI: 10.1017/jfm.2017.910
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration of elastic blades in oscillatory flow

Abstract: When subjected to a steady cross-flow, the deformation of flexible blades is known to result in the alleviation of the internal stresses in comparison to rigid structures. In the field of biomechanics, the flow-induced deformations of flexible structures leading to stress reduction have been often referred to as ‘reconfiguration’ in order to highlight the alleged benefits of such an adaptive process. In this paper, we investigate the reconfiguration of thin elastic blades and the resulting internal stresses wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…In this work, we only considered swimmers with a moderate length of the caudal fin, but it would be very engaging to tackle the effects of the deformation modes of long and flexible tails. [45][46][47]…”
Section: A Thrust Analysismentioning
confidence: 99%
“…In this work, we only considered swimmers with a moderate length of the caudal fin, but it would be very engaging to tackle the effects of the deformation modes of long and flexible tails. [45][46][47]…”
Section: A Thrust Analysismentioning
confidence: 99%
“…Their classification means that the shape of stem is independent of the magnitude of the oscillatory motion ( ). In addition to , Leclercq & De Langre (2018) found the non-dimensional parameters and . It is easy to realize that .…”
Section: Resultsmentioning
confidence: 97%
“…Leclercq & De Langre (2018) adopted another set of non-dimensional parameters: as the length scale and as the time scale; is the natural period of the submerged stem, where is the added mass of the submerged stem for a unit added mass coefficient. Leclercq & De Langre (2018) found that the product of the natural period and cyclic wave frequency describes the transition from ‘static’ regime to their ‘convective’ and ‘modal’ regimes for . They also defined a fourth regime named the ‘large-amplitude regime, static reconfiguration with fast reversal’ for .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blade motion due to flexibility reduces the relative velocity between flow and vegetation as well as the frontal area, resulting in a reduced drag that decreases velocity attenuation and wave attenuation in the vegetation meadow (Abdolahpour et al, 2018;Bouma et al, 2005;Houser et al, 2015;Mullarney & Henderson, 2010;Paul et al, 2012;Riffe et al, 2011;Rupprecht et al, 2017;Zeller et al, 2014). Numerical models have been developed to solve a force balance equation for the vegetation motion, considering gravity, buoyancy, structural damping, bending stiffness as restoring forces, as well as drag and inertia as driving forces (Ikeda et al, 2001;Leclercq & de Langre, 2018;Luhar & Nepf, 2016;Zeller et al, 2014;Zhu & Chen, 2015).…”
Section: Introductionmentioning
confidence: 99%